A Review and Psychometric Evaluation of Multidimensional Scales of Functional Impairment and Recommendations for Practice. Issue 3 (3rd July 2021) - Villarreal, Victor; Sullivan, Jeremy; Hechler, Joseph M.; Ruiz, Karen
Abstract: Assessment of functional impairment provides information that is complementary to diagnostic criteria information and is critical for identifying targets for intervention and evaluating treatment outcomes. This review presents summative psychometric information for five multidimensional measures of functional impairment developed for use with youths. Information for each measure, derived from manuals or test development articles, includes: (a) domains measured; (b) measure characteristics; (c) sample characteristics; (d) reliability; and (e) validity. Although each scale includes parent/caregiver forms and purports to measure the domains of school, social/getting along, and family relations, results indicate variability with regard to characteristics such as number of items, item content, sample characteristics, reliability/validity evidence, and interpretation of scores. Concluding recommendations address the use of such measures as part of the assessment process and includes specific examples in which it would be helpful to use formal measures of impairment.